Time-and-space modelling of public transport systems using GIS - Thorlacius, Per (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
Modelling the movement of vehicles and passengers in time and space in public transport systems is generally a rather complicated task. When finding the shortest path through a public transport network, not only the link impedance has to be taken into account, but also the time at which the link occurs, i.e. the time the bus actually rides the actual segment. This type of modelling requires an otherwise complex topological network. This paper describes how a geographic information system (GIS) can be used to create this kind of topology and how a model of a public trnaport system is implented.